Hypofractionated proton and carbon ion beam radiotherapy for sacrococcygeal chordoma (ISAC): an open label, randomized, stratified, phase II trial - Seidensaal, Katharina; Froehlke, Andreas; Hommertgen, Adriane; Lehner, Burkhard; Geisbüsch, Andreas; Meis, Jan; Liermann, Jakob; Kudak, Andreas; Stein, Katharina; Uhl, Matthias; Tessonnier, Thomas; Mairani, Andrea; et al. (Radiotherapy and oncology, 2024)
Introduction - Sacrococcygeal chordomas have high recurrence rates and are challenging to treat. - Methods - In this phase II prospective, randomized, stratified trial, the safety and feasibility of hypofractionated ion radiation therapy were investigated. The primary focus was monitored through the incidence of Grade 3-5 NCI-CTC-AE toxicity. Secondary endpoints included local progression-free (LPFS) and overall survival (OS). - Results - The study enrolled 82 patients with primary (87 %) and recurrent (13 %) inoperable or incompletely resected sacral chordomas from January 2013 to July 2022, divided equally into proton therapy (Arm A) and carbon ion beam therapy (Arm B) groups, each receiving a total dose of 64 Gy (RBE) in 16 fractions, 5-6 fractions per week. Overall 74 % of patients received no previous surgery and 66 % of tumors were confirmed by a brachyury staining. The mean and median Gross Tumor Volume at the time of treatment (GTV) was 407 ml and 185 ml, respectively. The median follow-up of the surviving patients was 44.7 months, and the 2-year and 4-year OS rates were 96 % and 81 %, respectively. Factors such as smaller GTV and younger age trended towards better OS. The LPFS after 2-year and 4-year was 84 % and 70 %, respectively. Male gender emerged as a significant predictor of LPFS. There was no significant difference between the treatment groups. We observed five grade 4 wound healing disorders (6 %). - Conclusion - The initial response rates were promising; however local control was not sustained. More comparative research on fractionation schemes is essential to refine treatment approaches for inoperable sacral chordoma.
Online verfügbar: 27. Juni 2024, Artikelversion: 3. Juli 2024
Gesehen am 10.01.2025